Attitude of Undergraduate Dental Students’ Toward Geriatric Oral Care in Davanagere City, Karnataka – A Cross-sectional Survey - Usha Govindaroy Venkatesh (Journal of the Indian Academy of Geriatrics, 2024)
Background: Population aging is a human success story. Getting older is associated with a higher incidence of chronic diseases which have proven to have oral manifestations. The future dentists should develop a positive attitude to provide care for elders. Objective: The objective of this questionnaire-based survey was to evaluate the attitude of undergraduate dental students’ toward elders in providing dental care to them. Materials and Methods: This cross-sectional study was conducted on 202 undergraduate dental students using a questionnaire including demographic characteristics and attitude sections. Data were fed into SPSS-20 and analyzed using descriptive statistics and independent t-test (α <0.05). Results: The mean age of students was 20.91 ± 1.56, 76.2% were female students, and 63.4% of students were in the clinical stage of their studies. The students’ mean score of attitude was 55.04 ± 5.81 (34–73). The mean score of attitude was not statistically different based on gender, age, year of study, type of family and bonding with grandparents. The “clinical training and discrimination in healthcare,” “compassion,” “adaptation to modern society,” and “resource distribution” were the four major factors extracted using principal component analysis and varimax orthogonal rotation method to measure attitude toward elders’ dental care. Conclusion: From our survey, it can be concluded that undergraduate students have moderately positive attitude toward elder patients. The four main components are the main areas in which dental education can be improved to better prepare aspiring dentists to treat elderly patients with high-quality dental care.